Musculoskeletal disorders among computer user workers in Ethiopia: a systematic review and meta-analysis - Biruk Demissie; Gebrehiwot Berie Mekonnen; Tigabu Munye Aytenew (Scientific Reports)
Abstract Musculoskeletal pain was the leading cause of physical injuries and disabilities, and ranking sixth among the top ten diseases in terms of global burden of disease. Approximately 9.5 million working days lost. Office workers including bank workers are vulnerable group for work related musculoskeletal disorders (MSDs) due to prolonged sitting, computer work, repetitive tasks, static posture, and uncomfortably working conditions. In Ethiopia, the annual prevalence of MSDs among computer users ranged from 55.2% to 77.6%. Previous primary studies presented inconsistent findings. Therefore, this review aimed to determine the pooled prevalence of musculoskeletal disorders and their associated factors among computer users in Ethiopia. We have extensively searched the PubMed, Cochrane, Web of Science databases, and Google Scholar for all available studies. All retrieved studies were exported to EndNote version 7 reference manager and analyzed using STATA version 17 statistical software. A weighted inverse-variance random-effects model was used to compute the overall MSDs among computer users. Publication bias was assessed using the funnel plot’s symmetry and a significant publication bias was identified using Egger’s test with a p-value of less than 0.05. The quality and risk of bias was evaluated using the quality rating standards of the Joanna Briggs Institute and risk of bias assessment tool respectively. The pooled prevalence of MSDs among computer users was 65.86% (95% CI 60.53, 71.18). The pooled prevalence of neck, shoulder, upper back, elbow, lower back, wrist/hand, hip/thigh, knee and ankle were 38.2% (95% CI 27.65, 48.77), 29.06% (95% CI 17.62, 40.49), 30.94% (95% CI 23.76, 38.11), 17.32% (95% CI 9.25, 25.38), 44.41% (95% CI 37.75, 51.06), 19.37% (95% CI 12.44, 26.30), 13.23% (95% CI 7.52, 18.95), 15.50% (95% CI 9.98, 21.01), and 13.34% (95% CI 8.32, 18.36) respectively. Being aged 30 and above 4.019 (95%CI: 1.92, 8.43), working in awkward posture 4.49 (95% CI: 2.66, 7.58), not doing physical exercise 3.43 (95% CI 2.1, 5.32), and prolonged computer work 2.56 (95% CI 1.34, 4.9) were significantly higher risk to MSDs. In Ethiopia, the overall prevalence of MSDs among computer users was significantly high. Therefore, employees should reduce the time spent on computers, engage in at least 150 min of exercise per week, and follow appropriate work practices and procedures while at work.